2010
DOI: 10.1103/physreve.81.016402
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dust-particle concentration on gas-discharge plasma

Abstract: A self-consistent kinetic model of a low-pressure dc glow discharge with dust particles based on Boltzmann equation for the electron energy distribution function is presented. The ions and electrons production in ionizing processes as well as their recombination on the dust-particle surface and on the discharge tube wall were taken into account. The influence of dust-particle concentration N(d) on gas discharge and dust particles parameters was investigated. It is shown that the increase of N(d) leads to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 23 publications
5
31
0
Order By: Relevance
“…This issue is considered in details in [25]. In spite of disperse particles deplete the high-energy wing of EEDF and influence the ionization efficiency of gas, however the observed in our experiment concentrations of particles could not lead to the EEDF depletion yet, as it was concluded in [16], nor change the electron temperature inside the dust cloud, as it show measurements represented in [7]. Still, at higher particle concentrations the effect of particle charge reduction observed in [7], should be also regarded.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…This issue is considered in details in [25]. In spite of disperse particles deplete the high-energy wing of EEDF and influence the ionization efficiency of gas, however the observed in our experiment concentrations of particles could not lead to the EEDF depletion yet, as it was concluded in [16], nor change the electron temperature inside the dust cloud, as it show measurements represented in [7]. Still, at higher particle concentrations the effect of particle charge reduction observed in [7], should be also regarded.…”
Section: Resultsmentioning
confidence: 48%
“…Another fruitful approach to the local problem is a solution of Boltzmann kinetic equation for EEDF. The selfconsistent kinetic model of a low pressure glow discharge with dust particles based on Boltzmann equation for EEDF and analysis of dependence of dust particle parameters versus particle concentration is represented in [16]. In [17] the EEDF on the axis of discharge tube and particle charge, radial electric field and electron distribution in nonequilibrium plasma of stratified glow discharge Experimental setup: 1 -glass discharge tube, 2 -cathode, 3 -anode, 4 -ring measuring probes, 5 -disperse particles, 6 -microscope, 7 -video camera, 8 -laser, 9 -thin laser beam, 10 -voltmeter, 11 -current meter, 12 -DC power supply, 13 -glass conical diaphragm, 14 -dust structure in discharge tube.…”
Section: Introductionmentioning
confidence: 99%
“…In these simulations, it has been observed that the presence of dust leads to an increase of the electron temperature as compared to the dust-free case. (It should be noted, however, that analytical calculations for a dusty DC discharge did not reveal any influence of the dust on the electron distribution function [32].) Land et al [10] determine an increase of electron temperature of about 0.2 eV for a large and dense 3D dust cloud under microgravity conditions.…”
Section: Time-averaged Behaviormentioning
confidence: 97%
“…There are many papers devoted to the influence of dust particles on gas discharge plasma parameters [1][2][3][4][5][6]. For the conditions of RF discharge used for thin films preparation, the influence of dust particles on discharge properties was investigated with the help of Particle-in-Cell Monte Carlo simulations by J.P. Boeuf [1] and later with the help of Boltzmann equation for EEDF by I. Denysenko et al [2].…”
Section: Introductionmentioning
confidence: 99%